2017
DOI: 10.1007/s40195-017-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Corrosion-Resistant Alloys in Concentrated Acids

Abstract: Nickel alloys containing optimum amounts of chromium (Cr), molybdenum (Mo) and tungsten (W) are widely used in the chemical processing industries due to their tolerance to both oxidizing and reducing conditions. Unlike stainless steel (SS), Ni-Cr-Mo (W) alloys exhibit remarkably high uniform corrosion resistance in major concentrated acids, like hydrochloric acid (HCl) and sulfuric acid (H 2 SO 4). A higher uniform corrosion resistance of Ni-Cr-Mo (W) alloys, compared to other alloys, in concentrated acids can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…The corrosion rate at 60 • C has a negative value during 24 h-60 h, and the value after 72 h is slightly smaller than that at 50 • C. It is assumed that the localized corrosion and adhering corrosion products result in the unusual fluctuation, which was observed in the research on Ni-Cr-Mo alloy corrosion [38,39]. Hence, the measurement and calculation of corrosion rate were misled by this highly localized deterioration and incomplete removal of corrosion products [70]. Specifically, the negative corrosion rate at 60 • C probably resulted from the additional corrosion products remaining after the cleaning process.…”
Section: Corrosion Rate Analysismentioning
confidence: 99%
“…The corrosion rate at 60 • C has a negative value during 24 h-60 h, and the value after 72 h is slightly smaller than that at 50 • C. It is assumed that the localized corrosion and adhering corrosion products result in the unusual fluctuation, which was observed in the research on Ni-Cr-Mo alloy corrosion [38,39]. Hence, the measurement and calculation of corrosion rate were misled by this highly localized deterioration and incomplete removal of corrosion products [70]. Specifically, the negative corrosion rate at 60 • C probably resulted from the additional corrosion products remaining after the cleaning process.…”
Section: Corrosion Rate Analysismentioning
confidence: 99%
“…A recent study [6,13] performed on a wide range of corrosion-resistant Ni-Cr-Mo and Ni-Cr-Mo-W alloys in various acidic solutions suggested that Mo (or Mo and W) forms a protective oxide in low pH-reducing acids (like HCl, H 2 SO 4 and H 3 PO 4 ), responsible for an enhanced corrosion resistance performance in Mo-rich alloys, Available online at http://link.springer.com/journal/40195 & Ajit Mishra ajitosu@gmail.com…”
Section: Introductionmentioning
confidence: 98%
“…Iron (Fe)-and nickel (Ni)-based alloys are widely used in aggressive environments because of their excellent corrosion resistance and high mechanical strength which can be attributed to their alloying compositions [1][2][3][4][5]. An addition of the optimum amounts of chromium (Cr), molybdenum (Mo) and tungsten (W) significantly increases the corrosion resistance in both reducing (like HCl, H 2 SO 4 ) and oxidizing environments (like HNO 3 ) as well as its resistance to localized corrosion [1,2,6]. For applications in HF and H 2 SO 4 , Fe-and Ni-based alloys containing Cu exhibit an enhanced corrosion resistance performance [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alloying elements can be added to Ni alloys to produce a wide variety of alloys such as Cr and Mo which give the alloys a high corrosion resistance [7][8][9][10]. If the Cr is sufficient enough, the Cr2O3 passive oxide layer is grown on the surface [11]. The use of Ni alloys as structural materials depends highly on the concentration and the proportion of alloying components, in particular Cr and Mo [12,13].…”
Section: Introductionmentioning
confidence: 99%